Parental programming: How can we improve study design to discern the molecular mechanisms?. (24th July 2013) - Lecomte, Virginie; Youngson, Neil A.; Maloney, Christopher A.; Morris, Margaret J.
<x xml:space="preserve">Abstract</x> The contribution of inherited non‐genetic factors to complex diseases is of great current interest. The ways in which mothers and fathers can affect their offspring's health clearly differ as a result of the intimate interactions between mother and offspring during pre‐ and postnatal life. There is, however, potential for some overlap in mechanisms, particularly epigenetic mechanisms. A small number of epidemiological studies and animal models have investigated the non‐genetic contribution of the parents to offspring health. Discovering new mechanisms of disease inheritance is technically difficult, especially in genetically, socially and environmentally heterogeneous human populations. Therefore, rigorous experimental design, appropriate sample numbers and the use of high‐throughput technologies are necessary to provide convincing evidence. Based on recent examples from the literature, here we propose several ways to improve human studies that aim to identify the underlying mechanisms of transgenerational inheritance of metabolic disease.